Effects of increased flooding on riparian vegetation: Field experiments simulating climate change along five European lowland streams - Garssen, Annemarie G.; Baattrup‐Pedersen, Annette; Riis, Tenna; Raven, Bart M.; Hoffman, Carl Christian; Verhoeven, Jos T. A.; Soons, Merel B. (Global change biology, 2017)
In many parts of the world, the magnitude and frequency of cold‐season precipitation are expected to increase in the near future. This will result in an increased magnitude and duration of winter and spring flooding by rain‐fed streams and rivers. Such climate‐driven increases in flooding are likely to affect riparian plant communities, but future vegetation changes are hard to predict due to current lack of data. To fill this knowledge gap, we experimentally modified the hydrology of five streams across three countries in north‐western Europe during late winter/early spring over a period of 3 years. We assessed the responses in riparian plant species richness, biomass, plant‐available nitrogen and phosphorus and seed deposition to increased flooding depth (+18 cm on average at the lowest positions along the riparian gradient) and prolonged flooding duration (6 weeks on average). After 3 years of increased flooding, there was an overall decline in riparian species richness, while riparian plant biomass increased. Extractable soil nitrogen and phosphorus also increased and are likely to have contributed to the increased biomass. Increased flooding resulted in the arrival of more seeds of additional species to the riparian zone, thereby potentially facilitating the shifts in riparian plant species composition we observed. The results of our concerted experimental effort demonstrate that changes in stream riparian plant communities can occur rapidly following increased winter flooding, leading to strong reductions in plant species diversity. An increased magnitude and duration of winter and spring flooding by rain‐fed streams and rivers are expected, likely affecting riparian plant communities. We experimentally modified the hydrology of five streams across three countries in north‐western Europe during late winter/early spring and assessed the responses in riparian plant species richness, biomass, plant‐available nitrogen and phosphorus and seed deposition to increased flooding depth and duration. After 3 years of increased flooding, there was an overall decline in riparian species richness, while riparian plant biomass, extractable soil nitrogen and phosphorus increased. More seeds of additional species were deposited in the riparian zone, potentially facilitating the shifts in riparian plant species composition we observed. Changes in stream riparian plant communities can occur rapidly following increased winter flooding, leading to reductions in plant species diversity.